-8r+6-8r=-10-8r

Simple and best practice solution for -8r+6-8r=-10-8r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8r+6-8r=-10-8r equation:



-8r+6-8r=-10-8r
We move all terms to the left:
-8r+6-8r-(-10-8r)=0
We add all the numbers together, and all the variables
-8r-8r-(-8r-10)+6=0
We add all the numbers together, and all the variables
-16r-(-8r-10)+6=0
We get rid of parentheses
-16r+8r+10+6=0
We add all the numbers together, and all the variables
-8r+16=0
We move all terms containing r to the left, all other terms to the right
-8r=-16
r=-16/-8
r=+2

See similar equations:

| 4y=3(10-2y) | | 1+6n=n-5+7n | | f(24)=16+f(16)+12 | | -7+8x+3x=8x+4x | | -1/2+2/3y=-8/5 | | 5b+5+5b=-7+8b | | x=44-334 | | 2x+2x=8+6x | | 0=625-20s | | 1-5n=-8n+3n+1 | | 〖4x〗^2-16=0 | | 36x+6=6x | | 5.68/j=071 | | 8.5+(1-2.5k)=-24.5 | | 375=10x+2x | | 4=t+8/7 | | 0.20x1-0.8x2=0 | | 5s-7=43 | | (6x+1)=104 | | -26+8y=3(6y-5) | | (8x-4)=80 | | |3-(x-3)|=3 | | 25=2v-6v | | 25=2v+6v | | -9d-6+8d=-28 | | 10^(x+4)=12 | | -9d-6+8=-28 | | 3^2r-5=14 | | 4s+39=87 | | -1x^2+50x-400=0 | | Q=80-200p | | 2(9+8r)=-26 |

Equations solver categories